(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Iskandar BS, Iskandar J, Suroso, Alfian RL, Mulyanto D. 2022. Non-edible plants traded in traditional markets of Beringharjo, Yogyakarta and Pasar Baru, East Kalimantan, Indonesia: The role of biocultural system. Biodiversitas 23: 4657-4669. The trade of various non-edible plants in some traditional Indonesian markets has a close relationship with the biological and cultural diversity, as well as local knowledge of the community. Therefore, this study aims to examine the non-edible plant diversity used to make products sold in traditional markets, their various functions and parts, as well as the market chain. The study was conducted in Beringharjo, Yogyakarta, and Pasar Baru, Balikpapan, East Kalimantan to resemble regions with different cultural backgrounds. Data collection used the qualitative method with an ethnobotanical approach. The results showed that 25 species belonging to 16 families of non-edible plants were traded in the traditional markets of Beringharjo and Pasar Baru. The various parts being traded in both markets had numerous functions, including pilgrimage ceremonies at the cemetery, handicraft/decoration, and betel chewing. The market chain begins with farmers from villages, middlemen, traders in the traditional market, and then finally to consumers. The diversity of non-edible plants traded was determined by the biophysical and cultural aspects of the local community where the market is located. Therefore, traditional markets play an important role as hallmarks of a particular social culture by reproducing on a small scale the cultural and biological diversity. They are also essential in the acquisition and transmission of traditional knowledge of biodiversity.